Musculotendinous Disorders of the Abdomen and Pelvis - Kheterpal, Arvin B.; Palmer, William E.; Bredella, Miriam A. (Seminars in Musculoskeletal Radiology, 2017)
Musculotendinous disorders of the abdomen and pelvis are common causes of pain in both athletes and nonathletes. Magnetic resonance imaging (MRI) is the modality of choice in the work-up of these patients. This article focuses on the MRI appearance of normal anatomy and spectrum of musculotendinous disorders in the abdomen and pelvis including muscle strains and tears, avulsions and apophysitis, muscular contusions, athletic groin pain, and gluteal aponeurotic/proximal iliotibial band injuries. Normal biomechanics and injury mechanisms are discussed.
Keywords: musculotendinous disorders; abdominal wall imaging; side strain; athletic groin injury; athletic pubalgia